IMMUNIZATION AND CHILD NUTRITION FACTORS ON MEASLES INCIDENCE IN JRAKAH VILLAGE, BOYOLALI, 2025 - Presenta, Lorda; Aziza, Nur; Adi, Mateus Sakundarno; Suhartono, Suhartono; Kuncoro, Teguh Tri (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
On January 2025, the Selo Health Center reported seven measles cases at Jrakah Village. The study purposed to determine the relationship between immunization and nutritional status with measles outbreaks. This study used an analytical observational method with a 1:6 case-control study design. The sample of this study was 49 respondents who were selected using random sampling techniques in the at-risk population, and interviews and questionnaires were carried out for data collection. Data analysis was done using the Anthropocal calculator and the Chi-square test. The results of statistical analysis showed a relationship between basic immunization status (p-value = 0.041; OR = 8.824; 95%CI = 0.973 - 80.019), BIAS immunization status (p-value = 0.007; OR = 30.750; 95%CI = 2.562 - 369.092), and nutritional status (p-value = 0.016; OR = 9.867; 95%CI = 1.690 - 57.600) with a measles outbreak. Basic immunization status, BIAS immunization status, and nutritional status were risk factors for the measles outbreak at Jrakah Village. However, basic immunization status was not statistically significant as a risk factor for the measles outbreak at Jrakah Village. This could be due to the small number of samples and limited data in the study. Therefore, it is recommended that immunization coverage be increased and additional food (PMT) provided to improve nutritional status and minimize measles infection.